Evaluation of the antihyperglycemic, antilipidemic and antioxidant potential of Cucurbita ficifolia in human type 2 diabetes - Jain, Amita; Mishra, Meerambika; Yadav, Dhananjay; Khatarker, Dheeraj; Jadaun, Pratiksha; Tiwari, Arvind; Katare, Charu; Prasad, GBKS (Progress in Nutrition, 2018)
Background and Aim: The present study has been undertaken to analyze the antihyperglycemic, antilipidemic and antioxidant potential of Cucurbita ficifolia juice in type 2 diabetic subjects. Methodology: A total 34 subjects were selected for the study out of which 14 subjects were with type 2 diabetes mellitus, 10 subjects were selected as a normal control group and 10 subjects were selected as a normal treated group. The patients had type 2 diabetes for more than 2 years, their mean age was less than 45 years, and subjects were then asked to start the Cucurbita ficifolia juice therapy starting at day 0 and continuing up to 40 day both for diabetic and normal subjects. Fasting blood glucose, glycosylated hemoglobin, lipid profile and anti-oxidant levels were measured two times at 0 days and continuous 40 days Cucurbita ficifolia therapy. Results: This study compared the measurement of glucose levels, lipid biomarkers, antioxidant and lipid peroxidation in all three groups [normal control, normal treated, and type 2 diabetic patients treated], at 0 days and after therapy of 40 days with Cucurbita ficifolia juice. Conclusion: The results suggest that the Cucurbita ficifolia juice therapy in type 2 diabetes may have the potential to regulate hyperglycemia, hypercholesterolemia and enhance the antioxidants enzymes along with reduction of lipid peroxidation.